Analysis of Construction Management Functions in Commercial Building Development Projects in Medan City - Gultom, Roi Yanto; Nasution, Adinda Juwita; Fahri, Tengku Muhammad (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Commercial buildings are buildings that accommodate various commercial functions such as villas, hotels, resorts, trade, office space for rent, and others. according to its type, a commercial building is a building that is planned and designed to bring benefits to the owner and its users. On the basis of this premise, the design of commercial buildings considers nine aspects. the factors that must be considered in the construction of commercial buildings and the actions taken so that the construction management function has a significant effect on the success of internal commercial building construction projects project development from its understanding, construction management applies management functions to a project by utilizing resources effectively and efficiently to achieve project objectives. the main objective of construction management is to manage management functions effectively and efficiently so as to obtain optimal results in accordance with the agreement with the project owner. The sampling technique chosen was Interview/Questionnaire and Primary Data. In this study, a sample of25 respondents from several different construction service companies was required. based on Company Status, type of company, company work experience, aspects of work equipment, capital / finance, HR (Human Resources). Analysis of construction management factors in the construction of commercial buildings in the city of Medan. Analysis of questionnaire data taken from 25 respondents was processed with Microsoft Office Excel 2010.